The ideals of the East : - Okakura, Kakuzo (Tuttle, 1970)
Contents: This is a short but very concise introduction to Asian art by the author of The Book of Tea. Written from a Japanese perspective, and focusing on Japanese art, one of the major themes is the relationship between spirituality, particularly Buddhism, and the evolution of Asian art.